A Cross Sectional Survey on the Knowledge and Attitude towards the Use of Multivitamin Products among the Students of a Medical University in the U.A.E - Rina Rosalia,Sarah Panjwani,Asma Abdillahi Ali,Mohammed Muthana Hameed Al Hayali,Ahmad Mohammed Alahmad,Annie Shirwaikar,Arun Shirwaikar (Journal of Applied Pharmaceutical Science, 2017)
Background and Objective: The consumption of multivitamin products for their benefits towards maintenance of health has often been debated upon. This study attempts to assess the knowledge and attitude of the students of a medical university towards the use of multivitamin products.Materials and Methods: A descriptive cross-sectional questionnaire based study was conducted on 319 student participants of a medical university in the U.A.E. Data was analyzed using SPSS version 22 and Pearson Chi Square Test.Results: Among the 319 participants in the survey, 132 (41.6%) were less than 20 years and 185 (58.4 %) were ≥20 years. Pearson Chi-Square Test identified a statistically significant association between the participants’ knowledge of multi vitamin products and their age (p ≤0.001) and knowledge of multi vitamin products was found to be directly proportional to the age of the students. However, no significant association was found between the use of multivitamins and the students’ region of origin, living status and BMI.Conclusion: It was observed that as the students progressed through the years in the medical university, they became more informed about the uses, benefits as well as the adverse effects associated with multivitamins.
Keywords: Multivitamin,Multivitamin Products,Anemia,Adverse Effects.